Antagonistic Test of Endophytic Bacteria of Chili Pepper Roots Producing Siderophores and Hydrolase Enzymes against Plant Pathogenic Bacteria Ralstonia Solanacearum - Hidayati, Siti Nur Isnaini; Zulkifli, Lalu; Sedijani, Prapti; Rasmi, Dewa Ayu Citra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to test the ability of endophytic bacterial isolates of cayenne pepper roots (Capsicum frutescens) to produce siderophore compounds and protease enzymes and to test the antagonistic activity of endophytic bacterial isolates in controlling the growth of plant pathogenic bacteria (Ralstonia solanacearum). The stages in this study are isolation of endophytic bacteria from cayenne pepper roots, siderophore production test, protease enzyme activity test, and biochemical and physiological characterization of potential endophytic bacteria, antagonistic test of endophytic bacteria against the growth of Ralstonia solanacearum bacteria. Endophytic bacteria were isolated from cayenne pepper plant roots taken from Selong, East Lombok. Characterization of siderophore-producing isolates used the Arnow test method. The activity of bacterial protease enzymes was tested qualitatively on Skim Milk Agar solid media. The antagonistic activity test of endophytic bacteria against pathogenic bacteria was carried out using the Kirby-Bauer diffusion method. Characterization of endophytic bacteria was carried out by observing colony morphology, Gram staining, and biochemical tests. There were 3 isolates that were able to produce siderophores (catecholate type) with codes EC5, EC12, and EC15. Six isolates showed protease enzyme activity with codes EC3, EC4, EC5, EC7, EC11, and EC15, with the highest Proteolytic Index (2.02) shown by isolate EC4. There were 3 isolates that were able to inhibit the growth of Ralstonia solanacearum (EC4, EC5, and EC15), with the highest inhibitory power shown by isolate EC15 (3.67 mm). The results of the study indicate that endophytic bacteria from cayenne pepper plant roots have the potential as biopesticides in the future.